Postulating Trinitarian Orthodoxy in Book 8 of Paradise Lost: Identifying Milton’s “Presence Divine” as the Son, Considering God’s First Conversation with Adam Apart from De Doctrina Christiana - Urban, David V. (Renaissance and Reformation / Renaissance et Réforme, 2025)
Recent scholarship that either challenges Milton’s authorship of De Doctrina Christiana or argues that De Doctrina Christiana is Miltonic but should not be used as a gloss upon Paradise Lost opens up the possibility to interpret Milton’s epic without deference to the Antitrinitarian treatise. A close textual analysis of Adam’s interaction with the Presence Divine in Paradise Lost 8.295–499 reveals, first, that the Presence Divine, contrary to the prevailing view of Milton scholarship, is the Son of God as opposed to God the Father. Moreover, Milton’s presentation of the Presence Divine is strikingly Trinitarian—in tension with De Doctrina Christiana and contrary to the received interpretation in Milton scholarship—and notably consistent with orthodox Trinitarian writings concerning the Son of God throughout church history, particularly orthodox reformed writings from the sixteenth, seventeenth, and eighteenth centuries.